2015
DOI: 10.1590/0100-69912015002008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of varicose vein surgery with preservation of the great safenous vein

Abstract: OBJECTIVE: To evaluate the efficacy of surgical treatment of varicose veins with preservation of the great saphenous vein. METHODS: We conducted a prospective study of 15 female patients between 25 and 55 years of age with clinical, etiologic, anatomic and pathophysiologic (CEAP) classification 2, 3 and 4. The patients underwent surgical treatment of primary varicose veins with great saphenous vein (GSV) preservation. Doppler ultrasonography exams were carried out in the first and third months postoperatively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…Seven studies observed the relationship between truncal venous diameter and CEAP classification, 9e12,19,20 while four described its relationship to VCSS. 9,20,22,23 CEAP classification Consistently, all studies reported a positive correlation between truncal venous diameters and CEAP clinical class. Studies showed that GSV diameters increased with clinical class.…”
Section: Clinical Severitymentioning
confidence: 53%
See 3 more Smart Citations
“…Seven studies observed the relationship between truncal venous diameter and CEAP classification, 9e12,19,20 while four described its relationship to VCSS. 9,20,22,23 CEAP classification Consistently, all studies reported a positive correlation between truncal venous diameters and CEAP clinical class. Studies showed that GSV diameters increased with clinical class.…”
Section: Clinical Severitymentioning
confidence: 53%
“…In a very small cohort of 22 limbs, Barros et al also described a directly proportional relationship between these two parameters, but did not report specific statistical values. 22 Additionally, Mendoza et al were able to show significant correlations between every single component of the VCSS and GSV diameter at both the saphenofemoral junction and proximal thigh. 20…”
Section: Vcssmentioning
confidence: 96%
See 2 more Smart Citations
“…It revealed that surgeries were performed essentially in cases of isolated superficial venous insufficiency (53.1%) 8 . Surgical treatment, such as radical saphenectomy in patients with alterations in this vein, has an increasingly limited indication, considering its importance as a vascular substitute for several beds of the circulatory system 15 .…”
Section: Discussionmentioning
confidence: 99%